Analisis Digital Forensik Rekaman Kamera CCTV Menggunakan Metode NIST (National Institute of Standards Technology) - Desti Mualfah; Rizdqi Akbar Ramadhan (UIR PRESS, 2021)
Conventional crimes recorded on CCTV (Closed Circuit Television) cameras are increasing, every criminal who is proven to have committed a certain crime will be punished in accordance with statutory regulations. The problem is how a case recorded on a CCTV camera can be used as digital evidence. Digital evidence is closely related to ensuring data security, privacy and integrity while following the stages of the digital forensic identification process. The identification stage using the NIST (National Institute of Standard Technolog) method is used for investigations in finding information related to metadata on CCTV camera footage so that it can provide structured information, describe and process information obtained from digital forensic investigation sources that can be implemented into the Chain of Custody document which aims to be used as legal digital evidence in court